Mycobacterium marinum infections in humans and tracing of its possible environmental sources - Slany, Michal; Jezek, Petr; Fiserova, Vera; Bodnarova, Monika; Stork, Jiri; Havelkova, Marta; Kalat, Frantisek; Pavlik, Ivo (Canadian journal of microbiology, 2012)
The low frequency of nontuberculous mycobacterial infections, nonspecific symptoms for individual mycobacteria, and the lack of specific identification methods could alter correct diagnosis. This study presents a combined microbiology and molecular-based approach for Mycobacterium marinum detection in four aquarists with cutaneous mycobacterial infection. Simultaneously, ecology screening for M. marinum presence in the aquarists' fish tanks was performed. A total of 38 mycobacterial isolates originated from four human patients (n = 20), aquarium animals (n = 8), and an aquarium environment (n = 10). Isolate identification was carried out using 16S rRNA sequence analysis. A microbiology-based approach, followed by 16S rRNA sequence analysis, was successfully used for detection of M. marinum in all four patients. Animal and environmental samples were simultaneously examined, and a total of seven mycobacterial species were isolated: Mycobacterium chelonae , Mycobacterium fortuitum , Mycobacterium gordonae , Mycobacterium kansasii , Mycobacterium mantenii , Mycobacterium marinum , and Mycobacterium peregrinum . The presence of M. marinum was proven in the aquarium environments of two patients. Although M. marinum is described as being present in water, it was detected only in fish.
Keywords: RNA, Ribosomal, 16S; atypické mykobakteriální infekce; Humans; lidé středního věku; Middle Aged; zvířata; antibakteriální látky; Mycobacterium; RNA ribozomální 16S; ryby; Microbial Sensitivity Tests; Fishes; mikrobiální testy citlivosti; mužské pohlaví; Mycobacterium marinum; Environmental Microbiology; výsledek terapie; Clarithromycin; Treatment Outcome; ženské pohlaví; Animals; lidé; Anti-Bacterial Agents; Mycobacterium Infections, Nontuberculous; klarithromycin; Male; mikrobiologie životního prostředí; Female